Prevalence and Correlated Factors of Obesity, Overweight and Central Obesity in Southwest of Iran - Seyed Bahman GHADERIAN; Leila YAZDANPANAH; Hajieh SHAHBAZIAN; Ali Reza SATTARI; Seyed Mahmuod LATIFI; Sara SARVANDIAN (Tehran University of Medical Sciences, 2019)
Background: We assessed the prevalence of obesity, overweight, central obesity and their associated risk factors in an urban population in Ahvaz, southwest of Iran. Methods: This population-based cross-sectional study was performed via random cluster sampling method in 6 health centers in Iran in 2015. A questionnaire was completed by each individual. Results: Of 2575 participants, 1187 (46%) were men. Nearly 50% of the participants' level of education was high school or higher. About 82% of the population was married and about one-third had positive family history of parental obesity. The total prevalence of obesity, overweight, and central obesity were 26.5%, 38.7%, and 28.6%, respectively. The rate of obesity in men was lower than in women (P<0.001). The prevalence of obesity increased until the age of 60 yr in both genders and decreased thereafter except for central obesity in women, which increased without any lag. Low level of education, marriage, positive history of parental obesity and parity ≥five were associated with increased odds of obesity (OR=2.14(1.52, 3.00), OR=2.4(1.75, 2.99), OR=2.7(1.71, 3.2) and 4.16(2.17, 7.65), respectively). Conclusion: Obesity and overweight have a high prevalence in southwest of the country, increasing with age. Although several risk factors are associated with obesity, the prevalence of obesity and overweight can be reduced by controlling the risk factors in the community.